Electrical source of pseudothermal light - Tom A. Kuusela (AMER ASSOC PHYSICS TEACHERS, 2022)
We describe a simple and compact electrical version of a pseudothermal light source. The source is based on electrical white noise whose spectral properties are tailored by analog filters. This signal is used to drive a light-emitting diode. The type of second-order coherence of the output light can be either Gaussian or Lorentzian, and the intensity distribution can be either Gaussian or non-Gaussian. The output light field is similar in all viewing angles, and thus, there is no need for a small aperture or optical fiber in temporal coherence analysis. (C) 2018 American Association of Physics Teachers.